Optimal replacement policies of repairable systems subject to shocks. (19th February 2007) - Matis, Timothy I.; Rangan, Alagar; Thyagarajan, Dimple
We consider a repairable system subject to a sequence of randomly occurring shocks, each of which results in a random amount of damage to the system. There are k general repair actions available, out of which one is chosen at each instant of shock arrival. The distributions of successive operating times between shocks and successive repair times are degenerative and dependent on the repair actions chosen earlier. System failure takes place when the accumulated damage crosses a fixed threshold level. We discuss optimal replacement strategies under an N-policy and a T-policy.